Залізний реманент хліборобів із Ревного - Горбаненко, С.А.; Михайлина, Л.П. (Археологія і давня історія України, 2021)
У статті проаналізовано залізні знаряддя хліборобської праці з Ревнянської агломерації слов’ян
VIII—X ст. Проведено порівняльний аналіз матеріалів у географічному оточенні: в межах ареалу
райковецької культури, а також з-поміж синхронних та хронологічно близьких культур і пам’яток.
Зроблено висновок про високий рівень техніки землеробства. Iron agricultural tools from the Revne agglomeration
of Slavs of the 8th—10th centuries is analyzed in the paper.
The complex is one of the outstanding sites of the
Eastern Croats Slavic tribal group in the Ukrainian
Carpathian region (fig. 1). During ca. 50 years of stationary
and supervisory explorations almost complete
set of agricultural tools for primary and secondary tillage
and for harvesting has been accumulated.
The paper provides detailed description of the tools.
Comparative analysis of the materials in geographical
environment was carried out both in the area of Raiky
culture and synchronous and chronologically close cultures
and sites. Iron parts of plow-type tools certify a
high level of technical equipment for tillage. Asymmetrical
heads are inherent in bow ard. This plow-type tool
had the head with iron wide-bladed tip posed horizontally
to the ground and also knife coulter and mouldboard.
Arable tools of this type cutted and turned the
soil. Their use indicates the highest level of development
of technical capabilities of tillage in the area of
Raiky culture and synchronous archaeological cultures
(fig. 2—4, 9). Hoes of two types are presented: the socketed
items with a vertical open socket and those with
a horizontal solid socket. Both types are well-known
(the first type is much more common) but functionally
there is no difference between them. Their analogies
are common in the area of Raiky culture and synchronous
surrounding (fig. 5, 6, 9).
The harvesting process can be considered traditional
for the people of Raiky culture. However there are
insignificant differences comparing to the aggregate
data. Thus, scythes with a curved handle (mainly used
for haymaking and possibly for harvesting cereals with
a tight ear) have not yet been occurred in Revne. However,
such findings are generally much less common
than sickles (fig. 7—9).
The complex of iron agricultural tools shows the
highest level of development of agriculture in the people
of Raiky culture. Comparative analysis with other
cultural and ethnic groups of the late 1st millennium
AD in Central and Eastern Europe also shows that the
level of agriculture is close to the achievements of the
Saltiv culture.